1998
DOI: 10.1074/jbc.273.43.28305
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Murine Macrophage Growth by Oxidized Low Density Lipoprotein Is Mediated by Granulocyte Macrophage Colony-stimulating Factor

Abstract: We have examined whether certain secreted factor(s) is involved in oxidized low density lipoprotein (Ox-LDL)-induced murine macrophage growth. An antibody against granulocyte-macrophage colony-stimulating factor (GM-CSF) effectively inhibited Ox-LDL-induced macrophage growth by >80%. Ox-LDL as well as phospholipase A 2 -treated acetylated LDL enhanced mRNA levels and protein release of GM-CSF from macrophages, while neither acetylated LDL nor lysophosphatidylcholine (lyso-PC) showed such effects. The maximal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 51 publications
3
85
0
6
Order By: Relevance
“…67 Some studies have also reported a modifying effect of the activation response to LPS by oxLDL through SRA. 71,72 How these processes are exactly intertwined is not yet clear.…”
Section: February 2000mentioning
confidence: 99%
See 1 more Smart Citation
“…67 Some studies have also reported a modifying effect of the activation response to LPS by oxLDL through SRA. 71,72 How these processes are exactly intertwined is not yet clear.…”
Section: February 2000mentioning
confidence: 99%
“…This GM-CSF secretion was strongly reduced in SRA-deficient macrophages. 67 In the atherosclerotic lesion, this GM-CSF production in response to oxLDL may play a very important role in priming macrophage growth, in conjunction with other cytokines. In addition to this proliferative role for the SRA, more recently, SRA expression was shown to confer resistance of macrophages to apoptosis.…”
Section: Sra In Adhesion and Cell-cell Contactmentioning
confidence: 99%
“…These results suggested that inhibition of GM-CSF production by glucocorticoids might cause inhibition of Ox-LDL-induced macrophage growth. Our previous report 15 and the present study demonstrated that Ox-LDL could induce an increase in GM-CSF mRNA level and protein release. Moreover, our subsequent preliminary experiments using luciferase assay in which we examined the promoter activity of GM-CSF gene showed that Ox-LDL activated reporter gene expression, suggesting that Ox-LDL could enhance GM-CSF mRNA expression at transcription level.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of GM-CSF was determined by a commercially available GM-CSFspecific ELISA kit (sensitivity, 5 pg/mL, Amersham) using recombinant murine GM-CSF as a standard. 15 …”
Section: Elisa For Gm-csfmentioning
confidence: 99%
See 1 more Smart Citation